Human intramuscular dirofilariasis: The silent masquerader - Jangla, Sunayana Mukesh; Chaturvedi, Uma Pankaj; Pillai, Raji (Indian Journal of Case Reports, 2025)
Dirofilariasis is an uncommon zoonotic infection transmitted by mosquitoes. In humans, it generally presents as nodules in the lungs, subcutaneous tissue, peritoneal cavity, or eyes. However, the present case series is regarding adult worms of Dirofilaria repens recovered from the masseter muscle of two patients in the fourth decade of life. Diagnosis was given on the basis of worm morphology and histopathology and confirmed by polymerase chain reaction. Surgical excision of the worm was done and pharmacotherapy with diethylcarbamazine was given. This report is remarkable as these cases arrived with identical clinical presentations and resided in close proximity to each other. Such atypical infections should be borne in mind, especially in light of current climatic changes and emerging zoonotic infections.